1975
DOI: 10.1111/j.1151-2916.1975.tb11488.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystallizing the Grain‐Boundary Glass Phase on the High‐Temperature Strength of Hot‐Pressed Si3N4 Containing Y2O3

Abstract: The effects of fabrication variables on the high-temperature strength of hot-pressed Si3N4 containing 5 wt% Y203 were studied. Materials containing a crystalline grain-boundary phase, formed as a consequence of a high-temperature presintering heat treatment and identified as Si3N4.Y,03, had hightemperature strengths significantly superior to those observed for materials containing a glass phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0
3

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(55 citation statements)
references
References 4 publications
0
47
0
3
Order By: Relevance
“…The softening of the glassy phase is the major factor detrimental to their HT properties. There are two major strategies for improving the HT properties of Si 3 N 4 ceramics: (i) the crystallization of the secondary amorphous phase by a postheating treatment [18][19][20][21]30] and (ii) the use of more refractory RE oxide additives that can provide crystalline secondary phases with high melting points [24,25,[30][31][32][33][34][35][36][37]. Previous studies have suggested that out of the RE oxides, Yb 2 O 3 and Lu 2 O 3 are the best additives for improving HT resistance up to 1400 and 1500 • C due to the formation of crystalline Yb 4 Si 2 O 7 N 2 [24,25,32,33,36] and Lu 4 Si 2 O 7 N 2 [31,34,37] grain boundary phases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The softening of the glassy phase is the major factor detrimental to their HT properties. There are two major strategies for improving the HT properties of Si 3 N 4 ceramics: (i) the crystallization of the secondary amorphous phase by a postheating treatment [18][19][20][21]30] and (ii) the use of more refractory RE oxide additives that can provide crystalline secondary phases with high melting points [24,25,[30][31][32][33][34][35][36][37]. Previous studies have suggested that out of the RE oxides, Yb 2 O 3 and Lu 2 O 3 are the best additives for improving HT resistance up to 1400 and 1500 • C due to the formation of crystalline Yb 4 Si 2 O 7 N 2 [24,25,32,33,36] and Lu 4 Si 2 O 7 N 2 [31,34,37] grain boundary phases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Three groups of additives have been used [1, [5][6][7]: (a) oxides (MgO, ^2 Q 3> ^2°3 * Al2°3) > which do not form solid solutions with 813114; (b) oxide and non-oxide additives (BeO, BeSiN2, Al2C>3 + A1N, A1N + Y2°3) which do form solid solutions with Si3N4; and (c) non-oxide additives (863^, ZrN, ZrC, Zr + A1N, Mg3N2) which give higher viscosity grain boundary phases. Additives such as MgO result in a continuous, amorphous, magnesium silicate intergranular phase [8][9][10][11], whilst those containing Y203~Al203 additions may possess both crystalline and amorphous grain boundary phases [12][13][14][15]. The presence of a glassy grain boundary phase is deleterious to both the room temperature and elevated temperature mechanical properties of silicon nitride.…”
mentioning
confidence: 99%
“…Con este aditivo la mullita sinteriza por fase líquida, como cabe esperar a partir del diagrama de fases del sistema ternario SiO 2 -Al 2 O 3 -Y 2 O 3 , que ha sido publicado en un trabajo reciente 9 . En un sistema de micromorfología análoga a la mullita, como es el Si 3 N 4 , está bien documentado que la adición de Y 2 O 3 mejora la sinterización mediante la formación de líqui-dos [10][11][12] . A posteriori, la cristalización de la fase secundaria (fundamentalmente Y 2 Si 2 O 7 ) mediante tratamiento térmico da lugar a unas propiedades mecánicas mejores que las del material con fase secundaria en estado amorfo 6,11,13,14 .…”
Section: -Introducciónunclassified
“…En un sistema de micromorfología análoga a la mullita, como es el Si 3 N 4 , está bien documentado que la adición de Y 2 O 3 mejora la sinterización mediante la formación de líqui-dos [10][11][12] . A posteriori, la cristalización de la fase secundaria (fundamentalmente Y 2 Si 2 O 7 ) mediante tratamiento térmico da lugar a unas propiedades mecánicas mejores que las del material con fase secundaria en estado amorfo 6,11,13,14 . El objetivo fundamental de este trabajo es conocer el efecto que la presencia de fases vítreas tiene sobre la deformación plástica de la mullita policristalina en un rango típico de alta temperatura, y en particular como evoluciona la ductilidad.…”
unclassified